6 Exercise-based cardiac rehabilitation for coronary heart disease – an updated cochrane systematic review and meta-analysis. (21st November 2022) - Dibben, Grace O; Faulkner, James; Oldridge, Neil; Rees, Karen; Thompson, David R; Zwisler, Ann-Dorthe; Taylor, Rod S
Abstract : Background: Coronary heart disease (CHD) is the most common reason for referral to exercise-based cardiac rehabilitation (CR) globally. However, the generalisability of previous meta-analyses of randomised controlled trials (RCTs) is questioned. Aim: To undertake a contemporary, updated Cochrane systematic review and meta-analysis of exercise-based CR for CHD. Methods: Database and trial registry searches were conducted to September 2020, seeking RCTs of exercise-based interventions with ≥6 months' follow-up, compared with no exercise control for adults with myocardial infarction (MI), angina pectoris, or following coronary artery bypass graft (CABG), or percutaneous coronary intervention (PCI). Study outcomes (mortality, recurrent clinical events, health-related quality of life (HRQoL) and cost-effectiveness) were pooled using random-effects meta-analysis. Meta-regression was used to examine effect modification. Study quality was assessed using the Cochrane risk of bias (ROB) tool. Results: A total of 85 RCTs in 23, 430 participants with median 12 months follow-up were included. Overall, exercise-based CR was associated with risk reductions in cardiovascular mortality (RR: 0.74, 95%CI: 0.64 to 0.86, number needed to treat [NNT]: 129), hospitalisations (RR: 0.77, 95%CI: 0.67 to 0.89, NNT: 81), and MI (RR: 0.82, 95%CI: 0.70 to 0.96, NNT: 223). Increased HRQoL with CR participation and cost-effectiveness were demonstrated. There was no evidence for risk reductions in overall mortality (RR: 0.96, 95%CI: 0.89 to 1.04) or CABG (RR: 0.96, 95%CI: 0.80 to 1.15). No differential effects were found across different patient groups, CR delivery models, dose, follow-up, or ROB. Conclusion: This review confirms participation in exercise-based CR by patients with CHD reduces cardiovascular mortality, recurrent cardiac events, and hospitalisations and provides additional evidence supporting the improvement in HRQoL and the cost-effectiveness of CR.